Improving Students' Learning Activities and Abilities in Understanding the Information in the Text through Problem-Based Strategy with Group Discussion Technique - Yakobus Paluru (Universitas Negeri Malang, 2015)
Peningkatan Aktivitas dan Kemampuan Memahami Isi Bacaan Melalui Pembelajaran Berbasis Masalah dengan Teknik Diskusi Kelompok Abstract: The purpose of this research is to improve students' learning activities and the ability to understand the information in the text. The results showed that the ability to understand written information students has increased after gaining experience learning through problem-based strategy with group discussion techniques. The increase is due to the emergence of motivation and the interest of students who constructed through problem-based learning strategies with group discussion techniques. The increase in activity caused by the adjustment of learning to students' needs related to the topic of reading materials used in teaching and habits and learning styles that is performed by the students. Key Words: learning, the content of text, group discussion   Abstrak: Penelitian ini bertujuan untuk meningkatkan aktivitas belajar dan kemampuan siswa dalam memahami informasi yang ada dalam bacaan. Hasil penelitian menunjukkan bahwa kemampuan memahami informasi tertulis siswa telah meningkat setelah mendapatkan pengalaman belajar melalui strategi berbasis masalah dengan teknik diskusi kelompok. Terjadinya peningkatan aktivitas disebabkan munculnya motivasi dan minat siswa yang dibangun melalui strategi pembelajaran berbasis masalah dengan teknik diskusi kelompok. Peningkatan aktivitas disebabkan adanya penyesuaian pembelajaran dengan kebutuhan siswa yang berkaitan dengan topik materi bacaan yang digunakan dalam pembelajaran dan kebiasaan serta gaya belajar yang dilakukan oleh siswa. Kata kunci: pembelajaran, isi bacaan, diskusi kelompok